Representações sociais de gestantes sobre a realização do pré-natal na pandemia da covid-19 - SOUSA, Iderlania Maria de Oliveira (2023)
The gestational period is characterized by intense changes in the woman's life; experiencing the COVID-19 pandemic and being pregnant represents an association of gravity in the period of pregnancy marked by feelings of fear and uncertainty. Considering that pregnancy is a multidimensional process, it is believed that studies guided by the Theory of Social Representations can help health professionals in understanding the aspects that shape and influence the subjects' actions. Objective: to apprehend the social representations attributed by pregnant women regarding prenatal care during the COVID-19 pandemic. This is an exploratory, qualitative research, based on the Theory of Social Representations. 17 pregnant women who underwent prenatal care during the COVID-19 pandemic, attended in a Sanitary District in the city of São Luís-MA, in the year 2022, were interviewed. For data collection, a questionnaire with sociodemographic data was used. and obstetrics; use of an inducing term with the words “pandemic and prenatal care” to apply the Free Word Association Technique (TALP) and an interview script with guiding questions associated with prenatal care during the pandemic. The data associated with the TALP were analyzed using the IRAMUTEQ software, in order to verify the frequency and order of evocation of the terms, with a value of 3.17 associated with the intermediate frequency, and 2.95, with the Average Order of Evocations (OME). The participants were between 18 and 36 years old, of mixed race, with complete secondary education, housewives and with an income of up to one minimum wage. They were in the third trimester of pregnancy, third pregnancy, history of cesarean delivery without complications in pregnancy and/or childbirth. In the prototypical analysis, it was verified that the inducing term resulted in 85 evocations and 40 different words. The matrix generated as a result of the prototypical analysis revealed the core meanings, revealing the Social Representations of women about prenatal care during the COVID-19 pandemic, characterized by the terms “care”, “fear”, “isolation” and “difficulties”. This study made it possible to reveal the Social Representations of pregnant women about prenatal care during the COVID-19 pandemic, revealing their insecurity in relation to the pandemic and the consequences for their health and that of their child.